DOCTOR STRANGE AND THE SECRET DEFENDERS - Thomas, Roy, 1940-; Marz, Ron; Coates, Andre; Grindberg, Tom; Rockwitz, Mike (New York : Marvel Worldwide, 2016)
The Master of the Mystic Arts revives the original non-team - and this time they're more secret than ever To save the world from the threats they'll never know existed, Doctor Strange uses magical tarot cards to select the perfect team for every mission - and he's stacked the deck with all the greatest and grittiest heroes of the nineties to draw from -- Wolverine, Spider-Man, Captain America, Hulk, Scarlet Witch, Silver Surfer, Punisher, War Machine, Darkhawk, Sleepwalker, The Vishanti, they're all here - and plenty more besides - to face down macabre menaces both demonic and otherworldly. Evildoers like Roadkill, Dreadlox and Xandu wielding the Wand of Watoomb It's the Sorcerer Supreme and a gathering of heroes, defending the Earth - just don't tell anybody.
Contains material originally published in magazine form as Secret defenders #1-11."
Keywords: Strange, Stephen (Fictitious character) -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Comics (Graphic works); Superhero comics